Barreras de comunicación entre el personal de enfermería y los usuarios adultos de 20 a 64 años que acuden a ser atendidos en el centro de salud Simiatug del distrito de salud (02d01) del cantón Guaranda provincia Bolívar periodo septiembre 2016–febrero 2017 - Pucha Guailla, Verónica Elizabeth (2017)
Communication is an innate process in man, it is not something that has to be learned, since it is with you from the moment it is born, its purpose is to share ideas and feelings; What is achieved through signs and symbols such as the word in oral and written form, sign, gesture and image, is also considered as an interpersonal process consisting of action, reaction, interaction and transaction between the personnel of Nursing, users and family. The study was carried out at the Simiatug Health Center, with Users from 20 to 64 years of age and the Nursing Personnel, to establish which are the Barriers and factors that prevent an adequate Communication between the Users and the Personnel of Nursing , To propose strategies that help improve the process of Therapeutic Communication and satisfy the user. During the pre-professional internship of the Rotating Nursing Internship it was observed that the Nursing Personnel have difficulties to communicate with them, due to several factors among which can be mentioned the Language as the predominant Barrier, causing alterations in the Therapeutic Nurse- Patient. In order to carry out this research project we used several methods, including field research, which consists of collecting data directly from the place of events, in this case it was at the Simiatug Health Center, therefore, the testimonies, Surveys, interviews and direct and indirect observations, served to give a value judgment to the investigative work. To determine the size of the sample, the Finite Formula was applied, with the number of users attended monthly by different pathologies in the Simiatug Health Center, a total of 350 adult individuals from 20 to 64 years of age, of whom we worked With a sample of 61 users, using as a data collection instrument a questionnaire with open and closed questions, in order to know the factors that impede an adequate Therapeutic Communication The results obtained indicate that between the Nursing Personnel and the Users there are Barriers (Nursing Staff does not use understandable words during communication), Psychological (the Angry, Frightened User), and Sociocultural (Language, Emotional, It was determined that the most frequent causes that impede effective Communication with Nursing Personnel are: Noise, geographical accessibility, age, physical condition, use of words difficult to understand, patient attitude, language and customs, in addition The most relevant constraint that prevents an effective interaction between Health Personnel and Users is the Native Language of this population, since kichuwa prevails. Therefore it is recommended that Nursing Personnel become familiar with the use of keywords in the Kichuwa Language; Which will help improve the relationship with the User, and also strengthen the communication with the use of the presence of the TAPS, who are native to the area and know the Language, to better convey the message during the counseling to the Users. As a result of the research, a strategic communication plan is proposed to be implemented by the nursing staff of the Simiátug Health Center and to improve the nurse-patient relationship. KEY WORDS: Communication Barriers, Nursing Personnel, Users from 20 to 64 years old.